Карьера как социальный феномен: сущность, признаки, технологии построения - Альшевская, Н. (Социология: теория, методы, маркетинг, 2000)
Carrier, as social phenomenon, has been defined in the article according to the following aspects: personal and socio-cultural. For each of these aspects, there were characterized the main features of carrier, mechanisms and technologies of its construction. In particular, there has been described the technologies of one-step and multi-step carriers.